DOES SELF-ESTEEM INFLUENCE STUDENT ENGLISH PROFICIENCY TEST SCORES? - Bela Rizky Utami; Achmad Yudi Wahyudin (Journal of English Language Teaching and Learning, 2022)
As one of Indonesia’s most prominent foreign languages, English is essential in education. The importance of English is reflected in the fact that it is taught from elementary school through university and is even used as a requirement for graduation or employment. Passing the campus-provided English Proficiency Test is a graduation requirement for Teknokrat University students. As a result, learning and mastering English is an important step for students.When it comes to teaching English in the classroom, there are various factors to consider. Every student has their own individuality. Different personalities result in varying levels of comprehension. Students’ personalities vary enormously, yet self-esteem is important in influencing individuals. In short, students’ personalities can differ based on their self-esteem. As a result, students’ personalities are greatly influenced by their sense of self, affecting their learning. This study aimed to see if there is a relationship between undergraduate students’ self-esteem and their English Language proficiency test at Teknokrat University. The computation results show that the correlation coefficient was .454. This study revealed a moderately positive relationship between students’ self-esteem and their EPT scores. Thus, the greater their self-esteem, the better their EPT score.Keywords: English Learning, English Proficiency Test and Self-esteem